The use of incremental methods in the construction and processing of composite elements with complex geometry - Kaczorowska, Katarzyna; Jakubowski, Michał (Advances in Mechanical and Materials Engineering, 2022)
This paper presents the issues of the use of incremental methods in the construction and processing of composite elements with complex geometry, as a component of a wider project devoted to the construction of the AOS-H2 fuel cell cooling unit. Considering the small dimensions of composite parts (considering the application conditions of a given material), it was necessary to introduce 3D printing as an auxiliary technology both during lamination and processing of semi-finished products, as well as a cheaper and faster production alternative for pressure stamps. The use of incremental methods not only improved the quality of the finished product, but also it was necessary that some of the fan’s elements, contrary to popular opinion, could be made of carbon fiber on such a small scale (e.g. blades whose height did not exceed 50 mm). The introduction of 3D printing to work with a laminate made it possible to use the composite to build elements with complex geometry and relatively small dimensions.